Olga P. Mitrofanova (celebrating the 75th birthday) - E. V. Zuev; O. A. Lyapunova; E. K. Khlestkina (Труды по прикладной ботанике, генетике и селекции)
On June 3, 2023, we celebrated the 75th birthday of Olga Pavlovna Mitrofanova, Doctor of Biological Sciences, Chief Researcher of the VIR Department of Wheat Genetic Resources.